Prime editing in hematopoietic stem cells—From ex vivo to in vivo CRISPR-based treatment of blood disorders - Wolff, Jonas Holst; Mikkelsen, Jacob Giehm (Frontiers in Genome Editing, 2023)
Prime editing of human hematopoietic stem cells has the potential to become a safe and efficient way of treating diseases of the blood directly in patients. By allowing site-targeted gene intervention without homology-directed repair donor templates and DNA double-stranded breaks, the invention of prime editing fuels the exploration of alternatives to conventional recombination-based ex vivo genome editing of hematopoietic stem cells. Prime editing is as close as we get today to a true genome editing drug that does not require a separate DNA donor. However, to adapt the technology to perform in vivo gene correction, key challenges remain to be solved, such as identifying effective prime editing guide RNAs for clinical targets as well as developing efficient vehicles to deliver prime editors to stem cells in vivo. In this review, we summarize the current progress in delivery of prime editors both in vitro and in vivo and discuss future challenges that need to be solved to allow in vivo prime editing as a cure for blood disorders.